2005
DOI: 10.1002/pon.909
|View full text |Cite
|
Sign up to set email alerts
|

Benefits from an uncertainty management intervention for African–American and Caucasian older long‐term breast cancer survivors

Abstract: In a randomized controlled design, this study tested the efficacy of a theoretically based uncertainty management intervention delivered to older long-term breast cancer survivors. The sample included 509 recurrence-free women (360 Caucasian, 149 African-American women) with a mean age of 64 years (S.D.=8.9 years) who were 5-9 years post-treated for breast cancer. Women were randomly assigned to either the intervention or usual care control condition. The intervention was delivered during four weekly telephone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
160
1
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(176 citation statements)
references
References 63 publications
1
160
1
11
Order By: Relevance
“…Studies have identified that, as positive adjustment to health status occurs, tolerance for uncertainty can increase, reducing fear and emphasizing living life to the fullest now. [27][28][29] Because transitions facilitated re-framing and adjustment to the reality of illness, supporting patients and caregivers through this process might help to strengthen relationships, redefine roles, and reconstruct self-identity. 22 In addition, helping patients and caregivers understand transitions as a potential for anticipating new beginnings, such as a new phase of living with their illness, in addition to grieving and coming to terms with endings, may facilitate "transition agility," the ability to make transitions throughout the illness trajectory with minimal distress.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified that, as positive adjustment to health status occurs, tolerance for uncertainty can increase, reducing fear and emphasizing living life to the fullest now. [27][28][29] Because transitions facilitated re-framing and adjustment to the reality of illness, supporting patients and caregivers through this process might help to strengthen relationships, redefine roles, and reconstruct self-identity. 22 In addition, helping patients and caregivers understand transitions as a potential for anticipating new beginnings, such as a new phase of living with their illness, in addition to grieving and coming to terms with endings, may facilitate "transition agility," the ability to make transitions throughout the illness trajectory with minimal distress.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, alguns estudos têm indicado a possibilidade da sua eficácia (Mishel et al, 2005). Apesar desta indicação de melhoria o mesmo estudo também salienta que embora os pensamentos automáticos de possibilidade de reincidência não surjam constantemente nas sobreviventes, a ameaça de reincidência dificilmente é descartada (Mishel et al, 2005).…”
Section: Discussionunclassified
“…As intervenções psicossociais têm tido um contributo positivo no ajustamento emocional e funcional das pacientes com cancro da mama (Antoni et al, 2001). Vários estudos têm demonstrado a eficácia da terapia cognitivo-comportamental (e.g., Goedendorp, Knoop, Gielissen, Verhagen, & Bleijenberg, 2014) e da psicoeducação nomeadamente: na redução de sintomas depressivos (Barsevick, Sweeney, Haney, & Chung, 2002); no aumento do conhecimento sobre a doença e tratamentos (Okamura, Fukui, Nagasaka, Koike, & Uchitome, 2003); na minimização do distress e ansiedade (Trask, Paterson, Griffith, Riba, & Schwartz, 2003); no 485 www.sp-ps.pt aumento da perceção de autoeficácia (Pereira, Lima, Monteiro, Torres, & Caetano, 2014); na limitação das possibilidades de reincidência (Mishel et al, 2005); na utilização de estratégias de coping adaptativas (Souza & Araújo, 2010); e na melhoria da qualidade de vida (QdV) (Trask, Paterson, Griffith, Riba, & Schwartz, 2003). A intervenção psicológica realizada no formato de grupo tem sido a mais utilizada nos indivíduos com cancro sendo a sua eficácia comprovada na literatura (Venâncio, 2004).…”
unclassified
“…Regarding the CBT techniques, there are many different and useful techniques in CBT. Mishel et al [5] used cognitive reframing, cancer knowledge, communication and various coping skills, whereas Puentes [14] used correction of distortion of thinking and Penedo et al [20] used deep-breathing, guided imagery, and progressive muscle relaxation for patients. In the present study, we used emotional expression, problem-solving, distraction, daily scheduling, and psychological education.…”
Section: Discussionmentioning
confidence: 99%
“…However, this efficacy was shown for patients with symptoms and psychological problems or states that are likely to differ from those in patients undergoing treatment who are not terminally ill. Patients under treatment commonly have psychological distress, life anxiety, and depression or uncertainty [5], resulting in low self-esteem.…”
Section: Introductionmentioning
confidence: 99%